3m-5=m+3

Simple and best practice solution for 3m-5=m+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m-5=m+3 equation:


Simplifying
3m + -5 = m + 3

Reorder the terms:
-5 + 3m = m + 3

Reorder the terms:
-5 + 3m = 3 + m

Solving
-5 + 3m = 3 + m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
-5 + 3m + -1m = 3 + m + -1m

Combine like terms: 3m + -1m = 2m
-5 + 2m = 3 + m + -1m

Combine like terms: m + -1m = 0
-5 + 2m = 3 + 0
-5 + 2m = 3

Add '5' to each side of the equation.
-5 + 5 + 2m = 3 + 5

Combine like terms: -5 + 5 = 0
0 + 2m = 3 + 5
2m = 3 + 5

Combine like terms: 3 + 5 = 8
2m = 8

Divide each side by '2'.
m = 4

Simplifying
m = 4

See similar equations:

| 5x1/2x1x2/7 | | 2x+2x=84 | | w+20+s=288 | | 10(t-3)+4t=7(2t+3)-11 | | 24x^5-4x^4= | | (x-2)2x+4-(2)3x=2(x-2)x | | -17=4+3w | | 2(4+x)=48 | | 6(3x-2)+3(10-3x)-4(2x+1)=-3 | | -17=4+3x | | 0.24(10000)-0.02y=0.08(y+10000) | | 5=4a(7+9) | | 2(B+2)-(7+B)=-4 | | 2x+4/2-3x/x-2=x | | 4-2(2-x)=1-(1-x) | | -2w-6=-6(w-1) | | 3-2x-4=6x-5+2x | | 2(3+x)=44 | | 2(3+x)=43 | | 6x+23=24 | | 2(3+x)=45 | | 0.45(24)+0.05x=0.15(18+x) | | -(7y+2)-(-6y-5)=0 | | 2(3+x)=50 | | 2(3+x)=40 | | -2(4s-4)-8=-2(9s+9)-3 | | 2(3+x)=85 | | 2(y+3)=5y-9 | | 5x-3[7-2(6x-7)-3x]=50x-63 | | 7+9r-2=8r+25-4r | | 4(2+x)=80 | | 4(2+x)=78 |

Equations solver categories